Substitutes for leadership and their moderating effects on the relationship between leadership styles and followers outcomes - Wan Ismail, Wan Khairuzzaman (2012)
The substitutes for leadership theory has been accredited as leadership classic and has attracted myriad of empirical research in developed countries. However, empirical studies on this area is still lacking especially in some Asian economies. Therefore, the present study has been designed in a selected Asian country work settings in light of substitutes of leadership. Further, to ensure the occurrence of substitutes for leadership among the sampled groups, data were collected from diverse working professionals using the proportionate stratified random sampling technique. To determine the effects of substitutes for leadership on the relationship between leadership styles and followers' work outcomes, moderated multiple regression technique was applied. The results revealed that the number of significant moderator effects found by the current study were more than the cases in earlier studies. This may be due to high reliability scores of the moderator variables and independent variables. It is therefore concluded that substitutes for leadership play an important role at workplace in influencing the followers' behaviors other than the leadership. Finally, implications of the research findings and future research prospects were discussed.